High proficiency of colonic endoscopic submucosal dissection in Europe thanks to countertraction strategy using a double clip and rubber band - Jacques, Jérémie; Charissoux, Aurélie; Bordillon, Pierre; Legros, Romain; Rivory, Jérôme; Hervieu, Valérie; Albouys, Jérémie; Guyot, Anne; Ponchon, Thierry; Sautereau, Denis; Kerever, Sebastien; Pioche, Mathieu (Endoscopy International Open, 2019)
Background and study aims ESD in the colon is more challenging technically than in other locations. Here, we report the first comparative case series of colon ESD using a systematic countertraction strategy using two clips and a rubber band.Patients and methods Retrospective comparative study of classic versus countertraction colon ESD performed in colon ESD cases collected prospectively at Lyon Edouard Herriot Hospital and Limoges University Hospital from January 2016 until December 2017.Results The study included 192 cases (control = 76, countertraction = 116). Countertraction using the double clip and rubber band technique versus the control group resulted in a significant decrease in the procedure time (94.7 vs. 117 min; P = 0.004) and significant increases in procedure speed (28.2 vs. 16.7 mm2/min; P < 0.0001), en bloc resection rate (95.7 % vs. 76.3 %, P < 0.0001), and R0 resection rate (78.5 % vs. 64.5 %, P = 0.04).At an individual operator point of view, results varied between operators but the double clip countertraction strategy significantly increased the en bloc resection rate, R0 resection rate, and speed of dissection for each of the 4 operators.Conclusion Systematic countertraction using a double clip and rubber band facilitates colon ESD. This strategy should become the standard for colon ESD.